Impact of pharmacist-led educational intervention on knowledge of self-management among asthmatic patients: a prospective cohort study - Ahmad Khan; Saima Mushtaq; Amjad Khan; Nafees Ahmad; Shahzadi Sidra Saleem; Rubina Aman; Shahzadi Sadia Saleem; Ayesha Bibi; Saifullah Mehsud; Ivan R Green; Sheikh Abdur Rashid; Kifayat Ullah Shah (BMJ Open)
Objectives Poor control of asthma in the majority of patients could be partly due to their lack of knowledge concerning disease management, its triggering agents and when to seek advice from the healthcare provider. This study aims to assess the impact of pharmacist-led educational intervention on knowledge of self-management among asthmatic patients.Design A pre–post cohort study.Setting Outpatient department of a tertiary care hospital affiliated with Quaid-i-Azam University, Pakistan.Participants Approximately 265 adult asthmatic patients selected through a spirometry process, aged ≥18 years, were approached. 240 patients gave consent to participate in the study and were divided into control and treatment groups.Interventions The educational intervention consisted of individual patient counselling using educational material with time varied according to each patient’s comprehension and previous knowledge.Primary and secondary outcome measures Assessment consisted of a 14-item Asthma Self-Management Knowledge Questionnaire (ASMQ) quantifying a patient’s self-management knowledge through an ASMQ score and its change following an educational intervention.Results Disease self-management knowledge was low with an average raw ASMQ score of 4.1 (max 14); which equates to a transformed score of 29.34 (max 100) and the proportion of patients who correctly answered more than 50% of questions were 16.7% preintervention. More than half of the participants (55%) did not know that asthma cannot be cured. The administration of educational intervention protocols resulted in significantly improved level of knowledge of asthma self-management (<0.001) in the treatment group (mean ASMQ score improved from 4.20 to 9.77).Conclusion On baseline visit, patients possessed a poor knowledge about asthma self-management. Educational intervention protocols had a positive impact on improving patients’ knowledge about disease self-management. This would suggest that education and self-management skills should be seen as an integral component of asthma management and should be incorporated in structured patient care to achieve optimal asthma control.